2020
DOI: 10.18632/aging.202230
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms based on pre-operative parametric for prediction of short-term mortality in acute myocardial infarction patients treated invasively

Abstract: Objective Our aim was to develop and independently validate nomograms to predict short-term mortality in acute myocardial infarction (AMI) patients. Results There were 1229 AMI patients enrolled in this study. In the training cohort (n=534), 69 deaths occurred during a median follow-up period of 375 days. The C-index for 1-year mortality in the training group and the validation cohort was 0.826 (95%CI: 0.780 - 0.872) and 0.775 (95%CI: 0.695 - 0.855), respectively. Integrated Discrimination Improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… 35 In our previous studies, we have also found that a lower systolic blood pressure level at admission and a low level of free triiodothyronine are independently associated with the short-term outcomes in patients with AMI. 36–38 In the current study, hypotension and free triiodothyronine were not associated with the risk of VA. Therefore, more attention should be paid to blood glucose and renal function in patients with AMI.…”
Section: Discussionmentioning
confidence: 38%
“… 35 In our previous studies, we have also found that a lower systolic blood pressure level at admission and a low level of free triiodothyronine are independently associated with the short-term outcomes in patients with AMI. 36–38 In the current study, hypotension and free triiodothyronine were not associated with the risk of VA. Therefore, more attention should be paid to blood glucose and renal function in patients with AMI.…”
Section: Discussionmentioning
confidence: 38%
“…In our predictive task, the model that took all available patient characteristics represented by the proposed patient representation method as inputs showed a higher performance than other models on the same task in previous studies (AUROC, 0.973 vs 0.905 to 0.935 [19,[29][30][31]48]). This may be because the embedding representation contained a large number of diverse features extracted from a general EMR system, while many researchers selected AMI-related features with the assistance of clinical experts.…”
Section: Principal Findingsmentioning
confidence: 74%
“…Mortality risk prediction for AMI patients plays a crucial role in clinical work, helping doctors identify potential clinical factors, take early intervention measures based on timely alerts of patients’ adverse health statuses, and reduce the burdensome expenditure of related health care expenses. Therefore, researchers [ 19 , 29 - 31 ] have focused on building machine learning models for the outcome prediction of AMI patients, and most of them used specific clinical features, such as laboratory test results (eg, albumin), comorbidities (eg, diabetes), and demographic data (eg, gender).…”
Section: Introductionmentioning
confidence: 99%
“…First, the NRI was calculated in the training cohort. Referring to reported studies [ 18 , 33 ], we used 10% and 30% as thresholds to define risk classes for low-risk (< 10%), intermediate risk (10%-30%), and high-risk (> 30%) patients, and compared with the LR1 model (< 10% for low risk, 10%-30% for intermediate risk, and 30% for highest risk), the LR2 model predicted an NRI of 8.92% for in-hospital all-cause mortality (Fig. 6 A).…”
Section: Resultsmentioning
confidence: 99%